Inovasi Bitterballen dengan Vegetable Oatmeal Bitterballen untuk Menambah Variasi Menu di Dapoer Marclip - Suryana Suryana; Layla Qotrull Nada (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Bitterballen is a traditional Dutch snack shaped like a ball, primarily made from flour and milk. Classic bitterballen usually contain minced beef and cheese. Its crispy exterior and soft interior make it a popular snack. In this study, the author utilizes vegetables and oatmeal to create a delicious and healthy version of bitterballen. The processing of Vegetable Oatmeal Bitterballen is in collaboration with Dapoer Marclip. The purpose of developing this product is to assess the panelists' preferences regarding appearance, color, aroma, texture, and taste, as well as to establish recipe standards. This research employs a research and development method. Data collection was conducted through organoleptic tests involving 25 participants, including lecturers, industry representatives, and consumers. Based on the results from four trials, it can be concluded that the preference levels in the main test were as follows: appearance—44% very much liked, 56% liked; color—76% very much liked, 24% liked; aroma—56% very much liked, 44% liked; texture—68% very much liked, 32% liked; taste—80% very much liked, 20% liked. Thus, it is stated that this product is well-liked and accepted by the panelists. The appropriate standard recipe formula is: 105g flour, 20g butter, 40g onion, 7g garlic, 100g spinach, 50g carrots, 85g corn, 40g mozzarella, 80g rolled oats, 1 egg, 150ml UHT milk, 120ml water, 5g MSG, 3g pepper, and 4g salt. The author suggests that future researchers consider alternative snack recipes using vegetables and appealing colors.